Development of the Assessment of Coach Emotions systematic observation instrument: A tool to evaluate coaches` emotions in the youth sport context - Allan, V.; Turnnidge, J.; Vierimaa, M.; Davis, P.; Côté, J. (International Journal of Sports Science & Coaching, 2016)
Current research on emotions in sport focuses heavily on athletes` intrapersonal emotion regulation; however, interpersonal consequences of emotion regulation are garnering recent attention. As leaders in sport, coaches have the opportunity to regulate not only their own emotions, but also those of athletes, officials, and spectators. As such, the present study set out to develop an observational tool, demonstrating evidence of validity and reliability, for measuring coaches` overt emotions in the youth sport context. Categories were derived and refined through extensive literature and video review, resulting in 12 categories of behavioural content and eight emotion modifiers (Neutral, Happy, Affectionate, Alert, Tense, Anxious, Angry and Disappointed). The final coding system is presented herein, complete with supporting evidence for validity and reliability. As a tool for both researchers and practitioners in sport, the Assessment of Coach Emotions (ACE) offers enhanced insight into the contextual qualities underlying coaches` interactive behaviours. ABSTRACT FROM AUTHOR